Bilingual language acquisition in a minority context: using the Irish–English Communicative Development Inventory to track acquisition of an endangered language. Issue 2 (23rd February 2017) - O'Toole, Ciara; Hickey, Tina M.
ABSTRACT: This study investigated the role of language exposure in vocabulary acquisition in Irish, a threatened minority language in Ireland which is usually acquired with English in a bilingual context. Using a bilingual Irish–English adaptation of the MacArthur-Bates Communicative Development Inventories) [Fenson, L., V. A. Marchman, D. J. Thal, P. S. Dale, J. S. Reznick, and E. Bates. 2007. The MacArthur-Bates Communicative Development Inventories . 2nd ed. Baltimore: Brookes], longitudinal parent report data were collected from 34 children (19 girls and 15 boys) at 4-monthly intervals, resulting in 61 data points between the ages of 17–36 months. Language exposure estimates indicated that while the caregivers 'always' spoke Irish to the children, both languages were used in most households, with/among siblings and extended family. The children's vocabulary indicated that they were Irish-dominant in this age range, with more Irish words than English for all vocabulary categories. The analysis also showed no difference in Irish vocabulary scores between children who were 'usually' exposed to Irish compared to those with lower exposure rates to Irish. However, there was a significant effect for caregivers' reported use of English on children's English scores. The results are discussed in terms of the language input needed to maintain an endangered language and factors to take into account for establishing good estimates of language exposure in a minority language context.